Pengaruh Penambahan Jumlah User Terhadap Trafik Voice Over Ip Pada Jaringan Lte Menggunakan Network Simulator 2.33 - Muhammad Abrar; Anhar Anhar; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
One of networks which can support voice traffic is LTE. The purpose of this study is to analyze the effect increased number of user and other traffic to Voice over IP traffic in LTE Network. Simulation study is done by NS 2.33 (Network Simulator 2.33) which consist of two scenario. First scenario use 1 server, 1 gateway, 1 eNodeB with increased number of user until 65, on the other hand second scenario use 1 server, 1 gateway, 1 eNodeB with increased number of user until 65 and add constant bit rate traffic.The research shows that increased number of user will effect the value of average througput, average delay, and average jitter. Meanwhile adding constant bit rate traffic has more significant effect to the value of average delay and average jitter.The highest throughput in scenarios 1 and 2 is achieved with a value of 46714.6 kbps and 57113.3 kbps respectively. Futhermore the lowest delay in scenarios 1 and 2 achieved with a value of 0.053 ms and 0.102 ms. Finaly the lowest jitter in scenarios 1 and 2 achieved with a value of 0.0338503 ms and 0.0169908 ms.Keywords : LTE, NS 2, VoIP